National COVID-19 vaccine program progress and parents' willingness to vaccinate their children. Issue 12 (2nd December 2021) - Goldman, Ran D.; Bone, Jeffrey N.; Gelernter, Renana; Krupik, Danna; Ali, Samina; Mater, Ahmed; Thompson, Graham C.; Yen, Kenneth; Griffiths, Mark A.; Klein, Adi; Klein, Eileen J.; Mistry, Rakesh D.; et al.
ABSTRACT: Vaccinating children against COVID-19 is critical as a public health strategy in order to reach herd immunity and prevent illness among children and adults. The aim of the study was to identify correlation between willingness to vaccinate children under 12 years old, and vaccination rate for adult population in Canada, the United States, and Israel. This was a secondary analysis of a cross-sectional survey study (COVID-19 Parental Attitude Study) of parents of children 12 years and younger presenting to 12 pediatric emergency departments (EDs). Parental reports of willingness to vaccinate against COVID-19 when vaccines for children will be approved was correlated to country-specific rate of vaccination during December 2020–March 2021, obtained from ourworldindata.org. Logistic regression models were fit with covariates for week and the corresponding vaccine rate. A total of 720 surveys were analyzed. In Canada, administering mostly first dose to the adult population, willingness to vaccinate children was trending downward (correlation = −0.28), in the United States, it was trending upwards (correlation = 0.21) and in Israel, initially significant increase with decline shortly thereafter (correlation = 0.06). Odds of willingness to vaccinate in Canada, the United States, and Israel was OR = 0.82, 95% CI = 0.63–1.07, OR = 1.24, 95% CI = 0.99–1.56, and OR = 1.03, 95% CI = 0.95–1.12, respectively. A robust population-based vaccination program as in Israel, and to a lesser degree the United States, led to increasing willingness by parents to vaccinate their children younger than 12 years against COVID-19. In Canada, slow rate of vaccination of the adult population was associated with lower willingness to vaccinate children.